Hubungan Nilai Belanja Hedonis dengan Niat Pembelian Produk Diskon pada Merek Buttonscarves di Sumatera Barat - Maisyarah, Adzkiatul; Yahya, Lucky Mahesa; Desri, Syuryatman; N, Erizal (Ekonomis: Journal of Economics and Business, 2026)
This study aims to analyze the effect of hedonic shopping value on purchase intention of discounted products on the Buttonscarves brand in West Sumatra. The dimensions of hedonic shopping value studied include novelty, pleasure, praise from others, escape, and social interaction. A quantitative approach was used with a survey method through a questionnaire distributed to 169 respondents who were Buttonscarves consumers. The results of the analysis using the SmartPLS model showed that novelty, pleasure, and praise from others had a significant positive effect on purchase intention of discounted products. However, escape and social interaction did not show a significant effect. This study provides insight to companies regarding the importance of considering hedonic values in marketing strategies to increase consumer purchasing interest, especially on discounted products.